국내 식품자원의 비타민 D 함량 모니터링 - 임창완(Chang Wan Lim); 이준엽(Jun Yeop Lee); 정광은(Kwang Eun Jung); 원종은(Jong Eun Won); 곽병만(Byung-Man Kwak); 이기웅(Ki Woong Lee); 박진주(Jin Ju Park); 이상훈(Sang Hoon Lee) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
LC-MS/MS를 이용하여 국내 식품자원 237종(식물성 식품자원 101종, 동물성 식품자원 34종, 가공식품 102종)의 비타민 D 함량을 분석한 결과, 24종에서 비타민 D가 0.28~ 1270.30 μg/100 g 수준으로 검출되었다. 식물성 식품자원 101종 중 5종에서 검출되었으며 0.28~1270.30 μg/100 g 수준이었다. 동물성 식품자원 34종 중 15종에서 검출되었으며 0.57~9.72 μg/100 g 수준이었다. 가공식품 102종 중 4종에서 검출되었으며 0.31~0.94 μg/100 g 수준이었다. 비타민 D2가 검출된 것은 237종 중 8종으로 꽃송이버섯 자연건조에서 1,270.30 μg/100 g으로 가장 많이 함유하고 있었다. 비타민 D3가 검출된 식품은 17종이고, 건조 오징어 생것에서 9.72 μg/100 g으로 가장 많이 함유하고 있었다. Contents of vitamin D were analyzed by LC-MS/MS in 237 domestic foods in Korea. SRM 1849a was used as the quality control for the experiment. Vitamin D was detected only in 24 of the 237 foods, ranging from 0.28 to 1,270.30 μg/100 g in content. These include 5 of the 101 vegetable foods (0.28 to 1,270.30 μg/100 g), 15 of the 34 livestock and seafood (0.57 to 9.72 μg/100 g), and 4 of the 102 processed foods (0.31 to 0.94 μg/100 g) examined. Vitamin D2 was detected in 8 of the 237 foods, and naturally dried cauliflower mushroom was determined to have the maximum content of vitamin D2 (1,270.30 μg/100 g). Vitamin D3 was detected in 17 of the 237 foods, with dried Japanese flying squid having the highest content (9.72 μg/100 g). This study provides reliable results that can be used to update the Korea Food Composition Table. KCI Citation Count: 0